Partners - Roberts, Nora, 1950- author 465662 (Glasgow, UK : Mills & Boon, 2012)
He had wanted Laurel Armand for years -- though professionally she was his nemesis. But once the two rival reporters headed down to steamy New Orleans to investigate a murder, Matt Bates was determined to make his lovely adversary his willing partner in passion.